In vitro differentiation of the immortalized mesencephalic progenitor cell line CSM14.1 occurs independently from haematopoietic cytokines - Hovakimyan, M.; Spasova, M.; Wree, A.; Schmitt, O. (Cellular and Molecular Biology, 2010)
In vitro expanded neural precursor cells could provide a renewable source of dopaminergic (DAergic) neurons for cell replacement therapy. In the present study immortalized cell line CSM14.1 was investigated in vitro. Cells were derived from the ventral mesencephalic area of a 14-day-old rat embryo and immortalized retrovirally with the temperature-sensitive mutant of the SV40 Large T-antigen. We investigate the proliferation and differentiation of these cells under various culture conditions, at different temperatures and serum conditions. For differentiation were propagated cells at 39° C in medium supplemented with 1% FCS with or without cytokines. At chosen time points cells were investigated for the expression of different markers by western blot and immunocytochemistry. As controls cells cultured at 33° C with 10% FCS for 3 days were used. We have shown that serum reduction alone is not sufficient for CSM14.1-cells to stop proliferating and begin differentiation. Following serum reduction and elevation of the temperature cells changed their morphology began to express specific band of the neuronal marker NeuN. Following cytokines treatment the mean length of cellular processes increased from 319 to 385 µm per cell, whereas the expression of neuronal markers such as NeuN and TH was not markedly changed. In conclusion, the differentiation cocktail consisting of interleukin 1(Il-1), Il-11, leukaemia inhibitory factor (LIF) and GDNF, does influence the outgrowth of neuritis but does not change the expression of mature neuronal markers at the protein level in CSM14.1 cells.